Management of the N0 neck - Brennan, Peter (Henry Stewart Talks, 2017)
Patterns of spread of oral cancer, Prognosis with metastatic neck disease, Risk of occult metastasis, Predictors of metastasis, Tumour depth, Perineural invasion, Imaging of the node negative neck, Sentinel lymph node biopsy, Survival benefits of neck dissection